Deconstructing Ethnic Identity of Chinese Children in Northern Ireland - Feng-Bing, Monica (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2006)
This paper focuses on two groups of sub-ethnic Chinese children respectively migrating from Mainland China and Hong Kong to Northern Ireland. It examines their cultural narratives surrounding topics of their country of origin, their adopted society in Northern Ireland. The paper analyses not only the surface narratives themselves, but also the social, cultural and political context in which such dispositional narratives were nourished and made possible. Theoretically, the author uses BOURDIEU's concept of "habitus" as the analytical tool to interpret and explain such narrative dispositions. Methodologically, the author uses in-depth interviewing and observations to achieve a more objective and overall understanding of their cultural narratives.URN: urn:nbn:de:0114-fqs0604297